Dynamics of environmental communication research in sustainable development: Systematic literature review and bibliometric analysis VOSviewer - Ira Meike Andariyani; Yunia Wardi; Susi Evanita (Indonesia Auditing Research Journal, 2026)
This study aims to analyze the dynamics and trends of environmental communication research in sustainable development through the Systematic Literature Review (SLR) approach and bibliometric analysis using VOSviewer. Data were obtained from the Scopus database for the period 2017–2026 and analyzed using the PRISMA framework and the PICO approach to ensure the relevance of the literature. The results of the study show that there has been a significant increase in environmental communication publications in the past decade. The bibliometric analysis identifies four main clusters, namely strategic concepts, policy and impact, behavioral and social, and normative and institutional aspects. The findings also show the fragmentation of knowledge and the dominance of technocratic approaches that position communication as an instrument of behavior change. In addition, the environmental communication paradigm evolved from a linear model to a participatory, digital, and integrative approach. This research emphasizes the importance of developing a more holistic, critical, and multidisciplinary environmental communication model in supporting sustainable development.